Oral meropenem for superbugs: challenges and opportunities. Issue 2 (February 2021) - Raza, Aun; Ngieng, Shih Chen; Sime, Fekade Bruck; Cabot, Peter J.; Roberts, Jason A.; Popat, Amirali; Kumeria, Tushar; Falconer, James R.
Highlights: Meropenem is used to treat various infections, especially from drug-resistant bacteria. Meropenem administration demands specialized resources and trained nurses. Meropenem is only available as an injectable formulation due to its poor chemical stability and permeability across the gut. Oral meropenem can significantly reduce the cost and resources required to treat bacterial infections. Clever pharmacological and formulations strategies are required for the development of oral meropenem. Abstract : An increase in the number of multidrug-resistant microbial strains is the biggest threat to global health and is projected to cause >10 million deaths by 2055. The carbapenem family of antibacterial drugs are an important class of last-resort treatment of infections caused by drug-resistant bacteria and are only available as an injectable formulation. Given their instability within the gut and poor permeability across the gut wall, oral carbapenem formulations show poor bioavailability. Meropenem (MER), a carbapenem antibiotic, has broad-spectrum antibacterial activity, but suffers from the above-mentioned issues. In this review, we discuss strategies for improving the oral bioavailability of MER, such as inhibiting tubular secretion, prodrug formulations, and use of nanomedicine. We also highlight challenges and emerging approaches for the development of oral MER.